2018
DOI: 10.1002/app.47010
|View full text |Cite
|
Sign up to set email alerts
|

Reduced graphene oxide (RGO)‐induced compatibilization and reinforcement of poly(vinylidene fluoride) (PVDF)–thermoplastic polyurethane (TPU) binary polymer blend

Abstract: Compatible blends of nonreactive thermoplastic fluoropolymer, poly(vinylidene fluoride) (PVDF) and thermoplastic polyurethane (TPU) at 70/30 weight ratio, were prepared by utilizing the unique structural feature of reduced graphene oxide (RGO). Here, RGO acts as a compatibilizer as well as a reinforcing filler. RGO interacts with both polymers and reduces the interfacial tension between them, leading to compatibilization. RGO content in the blends was varied from 0 to 0.5 wt %, and the best result was found at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 48 publications
0
47
0
Order By: Relevance
“…The residual oxygen containing functional groups present in the rGO interact with PVDF nanomaterials and hybridize with SnO 2 . Between the PVDF and rGO molecules, three types of interaction occur 23 . First, the interaction between πelectrons of rGO and CH 2 dipoles of PVDF, second is the interaction between F/H atoms of PVDF with the OH group present in rGO, and third is the interaction between F/H atoms of PVDF with the carbonyl and carboxyl group present in rGO.…”
Section: Resultsmentioning
confidence: 99%
“…The residual oxygen containing functional groups present in the rGO interact with PVDF nanomaterials and hybridize with SnO 2 . Between the PVDF and rGO molecules, three types of interaction occur 23 . First, the interaction between πelectrons of rGO and CH 2 dipoles of PVDF, second is the interaction between F/H atoms of PVDF with the OH group present in rGO, and third is the interaction between F/H atoms of PVDF with the carbonyl and carboxyl group present in rGO.…”
Section: Resultsmentioning
confidence: 99%
“…has improved the mechanical and thermal properties of the blends in the presence of r‐GO. [ 20 ] The presence of r‐GO had also influenced the multifunctional properties of the prepared chitosan‐based hydrogels. [ 21 ] PU dispersions with specific soft segments in union with PVDF is reported to have imparted superior gas permeability.…”
Section: Introductionmentioning
confidence: 99%
“…For mixtures of incompatible polymers, there is a known interesting and practically significant phenomenon when solid filler particles concentrate at the interface between the polymer phases …”
Section: Introductionmentioning
confidence: 99%
“…For instance, its use allows obtaining electrically conductive polymer materials with a very low concentration of an electrically conductive filler . It has been demonstrated that the concentration of finely dispersed particles at the interface can raise the strength of incompatible polymer mixtures by several times . There is substantial experimental evidence of compatibilization of incompatible polymer mixtures due to the filler localizing at the interface between the polymer phases .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation